2019
DOI: 10.1007/s00432-019-02950-y
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cathepsin K diminishes prostate cancer establishment and growth in murine bone

Abstract: Background The processes of prostate cancer (PCa) invasion and metastasis are facilitated by proteolytic cascade involving multiple proteases, such as matrix metalloproteinases, serine proteases and cysteine proteases including cathepsin K (CatK). CatK is predominantly secreted by osteoclasts and specifically degrades collagen I leading to bone destruction. PCa and breast cancer preferentially metastasize to the bone. Importantly, CatK expression level is greater in PCa bone metastatic sites compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Furthermore, CTSK has been found poorly expressed in normal prostate and in the prostate epithelial cells, whereas the expression was higher in the non-metastatic LNCaP cells and even greater in C4-2B and PC3 cells, and in skeletal metastatic tumor as revealed by tissue microarray. To this extent, CTSK affirmed as a key factor specific in PCa skeletal metastasis and PCa-induced bone lesions in vivo [ 165 ]. In a study by Yu et al, the role of cathepsins in a multistage epithelial carcinogenesis was examined using K14-HPV16 transgenic mice.…”
Section: Cathepsins In Tumor Progressionmentioning
confidence: 99%
“…Furthermore, CTSK has been found poorly expressed in normal prostate and in the prostate epithelial cells, whereas the expression was higher in the non-metastatic LNCaP cells and even greater in C4-2B and PC3 cells, and in skeletal metastatic tumor as revealed by tissue microarray. To this extent, CTSK affirmed as a key factor specific in PCa skeletal metastasis and PCa-induced bone lesions in vivo [ 165 ]. In a study by Yu et al, the role of cathepsins in a multistage epithelial carcinogenesis was examined using K14-HPV16 transgenic mice.…”
Section: Cathepsins In Tumor Progressionmentioning
confidence: 99%
“…novel but yet a standardized and a reliable, precise therapeutic in order to be used to treat prostate cancers, eventually by facilitating complete recovery from even at the secondary stage of the prostate cancer (Liang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…CatK secretion from PCa cell lines (LNCaP, DU145) and macrophages participates in local invasion by mediating extracellular degradation [109,177]. Liang et al [178] reported that CatK expression occurs both in PCa cell lines (LNCaP, C4-2B, and PC3) and in PCa tissues. CatK protein and enzymatic activity has been detected in the human PCa cell lines by Western blot and a fluorogenic assay, respectively [109].…”
Section: The Role Of Cathepsins In Primary Bone Cancer and Metastasesmentioning
confidence: 99%
“…In the same tumor model, twice daily treatment with the CatK inhibitor CKI (50 mg/kg) resulted in osteolytic lesions that were 79% smaller than those of tumor-bearing mice treated with the drug vehicle, and in a 62% reduction in the skeletal tumor burden [204]. More recently, this inhibitor was used to treat C4-2B prostate cancer cells in the tibiae of SCID mice; it significantly inhibited the tumor establishment, reduced the tumor growth in the bone, and decreased the serum prostate-specific antigen, likely due to the noted inhibition of bone resorption demonstrated in vitro with the CKI treatment [178]. Interestingly, the inhibitory effects of the CatK inhibitor were enhanced when it was administered in combination with ZOL [178].…”
Section: Cathepsin Targeting In Secondary Bone Tumorsmentioning
confidence: 99%
See 1 more Smart Citation